Disordered mesoporous V/TiO2 system for ambient oxidation of sulfides to sulfoxides - Negi, Sanjay Singh; Sivaranjani, Kumarsrinivasan; Singh, Anand Pal; Gopinath, Chinnakonda S. (Applied Catalysis A-General, 2013)
High sulfide conversion and predominant sulfoxide yield has been observed with 0.1% vanadium doped disordered mesoporous Ti1-xVxO2 material at ambient and sub ambient temperatures using environmentally green H2O2 oxidant. Ti1-xVxO2 materials were prepared by one-pot solution combustion method in less than 15 min and thoroughly characterized by X-ray diffraction, HRTEM, Raman spectra and other physicochemical techniques. Different sulfides, such as, phenylsulfide, methyl-p-tolylsulfide, ethylsulfide, thioanisole, were converted into the corresponding sulfoxide. Isolated V5+ incorporated in the TiO2 lattice is likely to be the active species for the sulfide oxidation reaction. Catalyst recycling studies indicates the robustness of the catalyst. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Ambient oxidation; Combustion synthesis; heterogeneous catalysis; Hydrogen peroxide; Mesoporous TiO2; Sulfoxidation; Sulfoxide

Disordered mesoporous TiO2-xNx+Nano-Au: an electronically integrated nanocomposite for solar H-2 generation - Sivaranjani, Kumarsrinivasan; Rajaambal, Sivaraman; Das, Tanmay; Roy, Kanak; Bhattacharyya, Somnath; Gopinath, Chinnakonda S. (ChemCatChem, 2014)
We report on H-2 generation by photocatalysis driven by simulated white light by electronically integrated Au nanoparticles with multifunctional, disordered mesoporous TiO2-xNx (Au-NT) nanocomposites. Solar H-2 generation (1.5 mmolh(-1)g(-1)) from aqueous methanol has been demonstrated with Au-NT nanocomposites. The water splitting activity of Au-NT is attributed to the 21.1 ps lifetime of charge carriers observed from fluorescence lifetime measurements, which indicates a high electron-injection efficiency from nano-Au to the conduction band of TiO2, and hence charge separation as well as utilization. This is directly supported by the observation of a high photoluminescence emission intensity with Au-NT that highlights the energy transfer from nano-Au to TiO2. The p-n heterojunction observed between the Au (001) and TiO2 (101) facets helps to-wards the higher charge separation and their utilization. A low mesochannel depth (< 10 nm) associated with disordered mesoporous TiO2-xNx helps the charge carriers to move towards the surface for redox reactions and hence charge utilization. Visible-light absorption, as a result of the surface plasmon resonance of nano-Au, is observed in a broad range between 500 and 750 nm, which helps in harvesting visible-light photons. Finally, electronically integrated nano-Au with TiO2-xNx in Au-NT is evident from Raman and X-ray photoelectron spectroscopy measurements. All of these factors help to achieve a high rate of H-2 production. It is likely that a higher rate of H-2 production than that reported here is feasible by strategically locating Au clusters in porous TiO2 to generate hot spots through electronic integration.
Keywords: heterogeneous catalysis; Hydrogen; mesoporous materials; photochemistry; water splitting